1978
DOI: 10.1021/jf60218a050
|View full text |Cite
|
Sign up to set email alerts
|

Iron absorption by rats from nonprescription dietary iron supplements

Abstract: Absorption of iron from seven nonprescription dietary iron supplements was measured in both iron-replete and iron-depleted rats by use of the extrinsic label technique. Both ferrous and ferric forms of the radioactive extrinsic tracer iron were used; the iron was in the form of 59FeS04, 59FeC13, or f e r r~u s -~~F e gluconate. Of six products tested with both ferrous and ferric labels, significant differences in absorption measured by the two different labels were found for three products. This suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This deviation was imposed by physiological homeostasis of iron metabolism and did not represent true availability of iron. Johnson and Evans (1978) observed that absorption of ferrous sulfate in rapidly growing, iron-depleted rats approached 100%. In this study, HRE for the standard groups fed diets at suboptimal iron levels was near 100%, indicating that HRE in iron-deficiency anemic rats was equivalent to iron absorption rate and truly reflected iron availability.…”
Section: Discussionmentioning
confidence: 98%
“…This deviation was imposed by physiological homeostasis of iron metabolism and did not represent true availability of iron. Johnson and Evans (1978) observed that absorption of ferrous sulfate in rapidly growing, iron-depleted rats approached 100%. In this study, HRE for the standard groups fed diets at suboptimal iron levels was near 100%, indicating that HRE in iron-deficiency anemic rats was equivalent to iron absorption rate and truly reflected iron availability.…”
Section: Discussionmentioning
confidence: 98%